Quercetin/oleic acid-based G-protein-coupled receptor 40 ligands as new insulin secretion modulators. (October 2017) - Badolato, Mariateresa; Carullo, Gabriele; Perri, Mariarita; Cione, Erika; Manetti, Fabrizio; Di Gioia, Maria Luisa; Brizzi, Antonella; Caroleo, Maria Cristina; Aiello, Francesca
Aim: Management of Type 2 diabetes mellitus by diet is achievable at the early stage of the disease; patients usually underestimate this approach and an appropriate drug therapy is required.Results: Starting from quercetin and oleic acid, that have effect on insulin secretion, a small set of hybrid molecules was synthesized. Insulin secretion was evaluated in both in vitro and ex vivo models. AV1   was able to enhance insulin secretion dose dependently, behaving as a conceivable agonist of G-protein-coupled receptor 40.Conclusion:  AV1 represents an interesting tool that interacts with G-protein-coupled receptor 40. Further studies will be carried out to evaluate the exact binding mode, and also to enlarge the library of these antidiabetic agents.